Heterostructured cube Au–Ag composites for rapid Raman detection of antibiotic ciprofloxacin. (22nd December 2016) - Li, Menghua; Wu, Hao; Wu, Yiping; Ying, Ye; Wen, Ying; Guo, Xiaoyu; Yang, Haifeng
Abstract : Abuse of synthetic antibiotic ciprofloxacin (CIP) caused the diffuse of drug resistant or even multidrug‐resistant pathogen strains. It called for a rapid technique to detect the CIP residue level in food products and environment. Highly sensitive surface enhanced Raman spectroscopy (SERS) offering intrinsic fingerprint information of molecule could be developed to become a quick method for detecting trace targeted species. In this work, the inositol hexakisphosphate as a stabilizing agent can be also used to synthesize Au–Ag bimetal heterostructured cubes. Heterostructured cubes were employed as highly active SERS substrate, and based on a portable Raman system, a simple and reliable SERS method was proposed for direct detection of trace CIP in water and chicken wings. Limits of detection of CIP in water and chicken wings were 8 × 10 −8 and 2 × 10 −7  M respectively. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Au‐Ag heterostructured cubes (HSCs) made by UV irradiation had high SERS activity. Ciprofloxacin residue in chicken meats was determined by Au‐Ag HSCs‐based SERS method. The label‐free assay could be a suitable method for quality control of food safety.